Blind prediction of slope safety factors using machine learning - Fu-Hsuan Yeh; Wei Liang; Louis Ge; Cheng-Hsi Hsiao (European Journal of Environmental and Civil Engineering, 2026)

Influential factors on cyclic resistance of non-plastic and low-plastic silts - Min-Chien Chu; Meng-Heng Chiang; Huan-Yu Chou; Yu-Syuan Jhuo; Louis Ge; Chi-Chin Tsai (Soil Dynamics and Earthquake Engineering, 2026)

An analytical model for liquefaction-induced underground buried structure uplift with experimental validation - Fu-Hsuan Yeh; Chun-Yu Hsu; Louis Ge; Siau Chen Chian (Tunnelling and Underground Space Technology, 2026)

Simulation of Cutter Wear in Gravel Using a Discrete Element Method Approach - Pei-Yun Shu; Yi-Fan Chen; Tai-Tien Wang; Bin-Chen Benson Hsiung; Chen-Yuan Liao; Louis Ge (Geotechnical and Geological Engineering, 2026)

Advancing the state of the art of cyclic direct simple shear Testing: Histories, current status, challenges and future trends - Xin Kang; Zi-Rui Ma; Louis Ge (Soil Dynamics and Earthquake Engineering, 2025)

Geotechnical reconnaissance of Hualien Port after the 2024 ML 7.2 hualien earthquake - Hsuan-Chih Yang; Chun-Jia Huang; Yung-Yen Ko; Kuan-Yu Chen; Chi-Chin Tsai; Chun-Hung Lin; Yu Wei Hwang; Min-Chien Chu; Yu-Syuan Jhuo; Yu-Ting Hsueh; Shodai Okano; LeeYi Wang; et al. (Soil Dynamics and Earthquake Engineering, 2025)

Microproperty effects on mesoscale gravel strength parameters revealed by in situ direct shear test simulations using discrete element method - Pei-Yun Shu; Tai-Tien Wang; Chen-Yuan Liao; Louis Ge (Bulletin of Engineering Geology and the Environment, 2025)

Intranasal Delivery of Lithium Salt Suppresses Inflammatory Pyroptosis in the Brain and Ameliorates Memory Loss and Depression-like Behavior in 5XFAD Mice - Piplu Bhuiyan; Wenjia Zhang; Ge Liang; Bailin Jiang; Robert Vera; Rebecca Chae; Kyulee Kim; Lauren St. Louis; Ying Wang; Jia Liu; De-Maw Chuang; Huafeng Wei (Journal of Neuroimmune Pharmacology, 2025)
Background Alzheimer’s disease (AD) is a devastating neurodegenerative disease (AD) and has no treatment that can cure or halt the disease progression. This study explored the therapeutic potential of lithium salt dissolved in Ryanodex formulation vehicle (RFV) and delivered to the brain by intranasal application. We first compared lithium concentrations in the brain and blood of wild-type mice following intranasal or oral administration of lithium chloride (LiCl) dissolved in either RFV or water. The beneficial and side effects of intranasal versus oral LiCl in RFV in these mice were assessed and potential mechanisms underlying the efficacy of anti-inflammation and anti-pyroptosis in the brains were also investigated in both wild-type and 5XFAD Alzheimer’s Disease (AD) mice brains. Methods For the study of brain versus blood lithium concentrations, wild-type (WT) B6SJLF1/J mice at 2 months of age were treated with intranasal or oral LiCl (3 mmol/kg) dissolved in RFV or in water. Brain and blood lithium concentrations were measured at various times after drugs administration. Brain/blood lithium concentration ratios were then determined. For studying therapeutic efficacy versus side effects and their underlying mechanisms, 5XFAD and WT B6SJLF1/J mice were treated with intranasal LiCl (3 mmol/kg) daily, Monday to Friday each week, in RFV beginning at 2 or 9 months of age with a 12-week treatment duration. Animal behaviors were assessed for depression (tail suspension), cognition (fear conditioning and Y maze), olfaction (buried food test), and motor functions (rotarod) at the age of 5 and 12 months. Blood and brain tissue were harvested from these mice at 13 months. Blood biomarkers for the functions of thyroid (thyroid stimulating hormone, TSH) and kidney (creatinine) were measured using ELISA. Changes in protein expression levels of the endoplasmic reticulum Ca 2+ release channels type 1 InsP 3 receptors (InsP 3 R-1), malondialdehyde (MDA)-modified proteins and 4-hydroxy-2-nonenal (4-HNE), pyroptosis regulatory proteins (NLR family pyrin domain containing 3 (NLRP3), cleaved caspase-1, N-terminal of Gasdermin D (GSDMD)), cytotoxic (IL-1β, IL-18, IL-6, TNF-α) and cytoprotective (IL-10) cytokines and synapse proteins (PSD-95, synapsin-1) were determined using immunoblotting. Mouse body weights were monitored regularly. Results Compared to oral LiCl in RFV nanoparticles, intranasal treatment of WT mice with LiCl in RFV markedly decreased blood concentrations at the time range of 30–120 min. The ratio of brain/blood lithium concentration after intranasal lithium chloride in RFV significantly increased, in comparison to those after oral administration lithium chloride in RFV or intranasal administration of lithium chloride in water. Intranasal lithium chloride in RFV inhibited both memory loss and depressive behavior in adult and aged 5XFAD mice. Additionally intranasal treatment of aged 5XFAD mice with LiCl in RFV effectively suppressed the increases in InsP 3 R-1, intracellular oxidative stress markers (4-HNE-bound and MDA-modified proteins), pyroptosis activation proteins (NLRP3, cleaved caspase-1, N-terminal GSDMD) and cytotoxic cytokines (IL-1β, IL-6, TNF-α), but reversed the down-regulation of cytoprotective cytokine IL-10. Intranasal LiCl in RFV also alleviated the loss of the postsynaptic synapse proteins PSD-95, but not synapsin-1, in aged 5XFAD mice. Blood level of the kidney function marker creatinine was significantly increased in 5XFAD than in WT mice in an age-dependent manner and this elevation was abolished by intranasal delivery of LiCl in RFV. Intranasal LiCl in RFV for 12 weeks in both WT or 5XFAD mice did not affect blood biomarkers for thyroid function, nor did it affect smell or muscle function or body weight. Conclusion Intranasal administration of LiCl in RFV significantly decreased lithium blood concentrations and increased brain/blood lithium concentration ratio, in comparison to its oral administration. Intranasal administration of LiCl in RFV robustly protected against both memory loss and depressive-like behavior, while had no side effects concerning thyroid and kidney toxicity in 5XFAD mice. These lithium-induced beneficial effects were strongly associated with lithium’s suppression of InsP 3 R-1 Ca 2+ channel receptor increase, pathological neuroinflammation and activation of the pyroptosis pathway, as well as the loss of the synaptic protein PSD-95. Intranasal delivery of lithium salt in RFV could become an effective and potent inhibitor of pathological inflammation/pyroptosis in the CNS and serve as a new treatment for both AD-associated dementia and depression with minimal unwanted side effects including peripheral organ toxicity. Graphical Abstract Intranasal delivery of lithium salt in Ryanodex Formulation Vehicle (RFV) robustly protected against both cognitive dysfunction and depression-like behavior 5XFAD mice, with no side effects or organ toxicity on thyroid and kidney functions. These lithium-induced beneficial effects were strongly associated with lithium’s suppression of pathological elevation type I InsP3 receptors (InsP3R-1) Ca2+ channel receptor proteins, oxidative stress, pathological neuroinflammation and activation of the pyroptosis pathway (Increased proteins of NLRP3, cleaved caspase-1, N-terminal GSDMD, IL-1β and IL-18). Intranasal delivery of lithium salt in RFV could become an effective drug in treating AD.

Novel method to estimate horizontal variability of shear wave velocity through multichannel analysis of surface waves - Yen-Hsiang Chang; Chi-Chin Tsai; Louis Ge; Duhee Park (Engineering Geology, 2024)

Excess pore water pressure generation in poorly graded sands with varying particle shapes and relative densities - Min-Chien Chu; Chi-Chin Tsai; Louis Ge (Soil Dynamics and Earthquake Engineering, 2024)

Failure of engineering structures and associated geotechnical problems during the 2022 ML 6.8 Chihshang earthquake, Taiwan - Yung-Yen Ko; Chi-Chin Tsai; Jin-Hung Hwang; Yu-Wei Hwang; Louis Ge; Min-Chien Chu (Natural Hazards, 2023)

Strength variations due to re-liquefaction—indication from cyclic tests on undisturbed and remold samples of a liquefaction-recurring site - Fu-Kuo Huang; Chi-Chin Tsai; Louis Ge; Chih-Wei Lu; Chung-Chi Chi (Bulletin of Engineering Geology and the Environment, 2022)

Small strain moduli of compacted silt by ultrasonic pulse velocity measurements - David M. Weidinger; Honghua Zhao; Annie On-Lei Kwok; Xin Kang; Louis Ge (Marine Georesources & Geotechnology, 2020)

The critical state and steady state of sand: A literature review - Xin Kang; Zhao Xia; Renpeng Chen; Louis Ge; Xiaoming Liu (Marine Georesources & Geotechnology, 2019)

The accumulation and fractionation of Rare Earth Elements in hydroponically grown Phytolacca americana L. - Ming Yuan; Mei-Na Guo; Wen-Shen Liu; Chang Liu; Antony van der Ent; Jean Louis Morel; Hermine Huot; Wan-Ying Zhao; Xian-Ge Wei; Rong-Liang Qiu; Ye-Tao Tang (Plant and Soil, 2017)

Assessment of empirical equations for the compression index of fine-grained soils in Missouri - Site Onyejekwe; Xin Kang; Louis Ge (Bulletin of Engineering Geology and the Environment, 2015)

Structure, redox, pK a, spin. A golden tetrad for understanding metalloenzyme energetics and reaction pathways - Louis Noodleman; Wen-Ge Han (JBIC Journal of Biological Inorganic Chemistry, 2006)